2010
DOI: 10.1002/fam.1068
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of thermoplastic composites filled with γ‐boehmite for fire resistance

Abstract: SUMMARYThis paper explores the use of boehmite as a fire retardant in low-density polyethylene and polyamide 6. The structure and morphology of the filler are characterized by X-ray diffraction and scanning electron microscopy. The water content of our boehmite is estimated about 30% by thermogravimetric analysis. The filler/matrix interactions in nanocomposites are investigated by means of thermo-physical measurements: differential scanning calorimeter and thermogravimetry. The resulting morphology shows part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In particular, the aggregates of BA give perfectly spherical submicronic particles in the case of LLDPE-D80-4 composite ( Figure 1f). As reported by Droval, this is probably due to a memory form effect coming from the aerosol droplets before drying, resulting in each particle considered as a highly concentrated nano crystallites boehmite aggregates linked together through a water-rich amorphous phase [36]. The XRD diffractograms of BA nanopowders and LLDPE nanocomposites are given in Figure 2a and 2b, respectively.…”
Section: Mechanical Testsmentioning
confidence: 61%
“…In particular, the aggregates of BA give perfectly spherical submicronic particles in the case of LLDPE-D80-4 composite ( Figure 1f). As reported by Droval, this is probably due to a memory form effect coming from the aerosol droplets before drying, resulting in each particle considered as a highly concentrated nano crystallites boehmite aggregates linked together through a water-rich amorphous phase [36]. The XRD diffractograms of BA nanopowders and LLDPE nanocomposites are given in Figure 2a and 2b, respectively.…”
Section: Mechanical Testsmentioning
confidence: 61%
“…Poly(vinyl alcohol) (PVOH) considered as environmentally friendly is a good choice for polymer coating due to its good adhesion property with substrate, no need solvent in coating process, and its charring behavior during burning. As other metal hydroxides, boehmite and pseudo-boehmite have already used to impart flame retardancy in a couple of polymers: ethylene-vinyl acetate copolymer [18,19], polycarbonate/acrylonitrile butadiene-styrene blend [20], poly(methyl methacrylate) [21], polyethylene [22], polyamide 6 [22], polyamide 11 [23], polyester [24,25], polyethersulfone [26] or PVOH [27]. As both boehmite and PVOH are hydrophilic, boehmite can be incorporated into PVOH without pretreatment, only by simply dispersing the two components in water.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Zhang et al 27 showed a significant improvement in thermal stability of PE terephthalate in the presence of BA nanoparticles. Droval et al 28 studied the effect of BA on the fire retardance property of LDPE and polyamide 6 (PA-6). They found that the fire burning time was improved for LDPE and PA-6, respectively, at only 2 wt% of BA.…”
Section: Introductionmentioning
confidence: 99%
“…Droval et al. 28 studied the effect of BA on the fire retardance property of LDPE and polyamide 6 (PA-6). They found that the fire burning time was improved for LDPE and PA-6, respectively, at only 2 wt% of BA.…”
Section: Introductionmentioning
confidence: 99%